Comparison of Dacryocystorhinostomy with Mitomycin C Against Dacryocystorhinostomy with Intubation - Hassan Raza Jafri, Nazia Qidwai (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the surgical outcome of Dacryocystorhinostomy (DCR) with Mitomycin C (MMC) against Dacryocystorhinostomy with Intubation in patients of Nasolacrimal duct block (NLDB). Material and Methods: This randomized controlled trial was conducted on 130 patients with NLDB, equally and randomly enrolled in two groups. In Group A patients underwent DCR with intubation and in group B DCR with MMC from July 2009 to December 2009. Patients were followed for 06 months. The main outcome measures were assessment of regurgitation and the patency of lacrimal drainage system (LDS). Results: 130 patients of NLDB included in this study. Out of 65 patients in group A, 62 (95.4%) patients remained symptom free whereas, 3 (4.6%) showed failed syringing at the end of 6 months. However, out of the 65 patients in group B, 59 (90.8%) patients remained symptom free and 6 (9.2%) showed failed syringing. The overall success rate was 93.1%. (Statistics were and are mentioned in the results). Conclusion: Silicon tube and MMC, both yield equally successful results with DCR. However, use of MMC is more cost and time effective than silicon tube and also associated with lesser intra-operative and post-operative complications.